2009
DOI: 10.1021/ma802457v
|View full text |Cite
|
Sign up to set email alerts
|

Nanomorphology of Bulk Heterojunction Organic Solar Cells in 2D and 3D Correlated to Photovoltaic Performance

Abstract: Control of the nanoscale morphology of the donor-acceptor material blends in organic solar cells is critical for optimizing the photovoltaic performances. The influence of intrinsic (acceptor materials) and extrinsic (donor:acceptor weight ratio, substrate, solvent) parameters was investigated, by atomic force microscopy (AFM) and electron tomography (ET), on the nanoscale phase separation of blends of a lowband-gap alternating polyfluorene copolymers (APFO-Green9) with [6,6]-phenyl-C 71 -butyric acid methyl e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…13). 81,82 A clear picture of phase separation governed by these parameters was obtained. TEM showed that different kinds of fullerene derivatives had a strong effect on the morphology, which was explained by the differences in their solubilities.…”
Section: Polyfluorene-based Polymermentioning
confidence: 89%
See 1 more Smart Citation
“…13). 81,82 A clear picture of phase separation governed by these parameters was obtained. TEM showed that different kinds of fullerene derivatives had a strong effect on the morphology, which was explained by the differences in their solubilities.…”
Section: Polyfluorene-based Polymermentioning
confidence: 89%
“…The degree of phase separation between the polymer and PCBM had attracted a lot of attention. In the case of APFO-Green 9:PCBM blends, 81 a few processing parameters were taken into account, including the blend ratio of the polymer to PCBM, the nature of the substrates, solvents and acceptor materials, to optimize the morphology. Atomic force microscopy (AFM) and transmission electron microscopy tomography (TEMT) were used to examine the surfaces and bulk morphologies of thin films of the blend (Fig.…”
Section: Polyfluorene-based Polymermentioning
confidence: 99%
“…Increasing or decreasing solubility of a polymer through manipulation of the amount and types of side chains have a pronounced effect on blend morphology. [12,50,51] 6. Photovoltaic Device Engineering Using Interfaces and Geometries…”
Section: Progress Reportmentioning
confidence: 99%
“…The choice of electron donor and acceptor materials for use in BJH devices and their loading ratio is the first important step towards solar cell optimization. The choice of solvents is another important step [15]. It has a strong impact on the nano-scale morphology of the active layer, which plays an important role in the performance of solar cells [16] and OFETs [17].…”
Section: Resultsmentioning
confidence: 99%